1996
DOI: 10.1074/jbc.271.42.26143
|View full text |Cite
|
Sign up to set email alerts
|

Divalent Cations and Heparin/Heparan Sulfate Cooperate to Control Assembly and Activity of the Fibroblast Growth Factor Receptor Complex

Abstract: Polypeptides of the fibroblast growth factor (FGF) family are ubiquitous bioregulators within tissues whose activity is controlled by heparan sulfates within the pericellular matrix. FGF and the ectodomain of their transmembrane tyrosine kinase receptors (FGFR) exhibit heparin-binding domains that when juxtaposed in a FGF middle dotFGFR complex can accommodate a single, potentially bivalent, decameric polysaccharide chain in a ternary complex. Here we show that the interaction of heparin with FGF ligands is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
98
1
1

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 43 publications
7
98
1
1
Order By: Relevance
“…The importance of this property to biological activity remains to be established. A third model proposes that heparan sulphate molecules bind to both the growth factor and the receptor [78,104,105]. This provides a potential explanation for the finding that stimulation of bFGF binding to receptor requires a minimum heparan sulphate length of 10-12 monomer units [34].…”
Section: Modulation Of Growth-factor-receptor Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of this property to biological activity remains to be established. A third model proposes that heparan sulphate molecules bind to both the growth factor and the receptor [78,104,105]. This provides a potential explanation for the finding that stimulation of bFGF binding to receptor requires a minimum heparan sulphate length of 10-12 monomer units [34].…”
Section: Modulation Of Growth-factor-receptor Activationmentioning
confidence: 99%
“…It has been suggested that the extra length is required to generate a bifunctional agent that binds growth factor and receptor simultaneously. Binding of some FGF receptor isoforms to heparan sulphate has been demonstrated [104], although this has been reported to be dependent on high concentrations of magnesium (25 mM) [105]. Additional experimental evidence will be required before this model can be generally accepted.…”
Section: Modulation Of Growth-factor-receptor Activationmentioning
confidence: 99%
“…For FGFs, HS has been shown to directly facilitate ligand signaling in at least two ways: 1) ligand-HS interaction, which facilitates ligand dimerization (and in turn promotes receptor dimerization) and transactivation (33,34), and 2) receptor-HS interaction, which facilitates ligand-receptor interaction and consequently receptor activation (23,35). As K1 does not bind heparin, we examined whether heparin facilitated K1 signaling through direct and ligand-independent interaction with c-Met.…”
Section: C-met Binds Tightly To Hs Via Its Extracellular Domain-mentioning
confidence: 99%
“…The involvement of zinc or other metal cations in the binding of heparin to proteins is quite common, although the ions enhancing or inhibiting the reactions differ between systems [33][34][35][36]. The mechanism by which zinc enhances the binding of IL-5 to heparin is unknown.…”
Section: Discussionmentioning
confidence: 99%